Research of Semi-active Damper Control - DAI Ren-de; QIAN Hua; ZHAO Chang-long; LI Hai-tao; CUI Zhi-guo (机车电传动)
According to theoretical research and product development for railway vehicle semi-active damper, method to get frequency and amplitude of vibration velocity with vibration acceleration was proposed. Based on fuzzy neural network control strategy, damping parameters adjustable for semi-active damper control was achieved, which adapt all kinds of railway conditions and running speeds to fulfill the demand of speed up and comfortable quality.